Post-weaning Environmental Enrichment, But Not Chronic Maternal Isolation, Enhanced Ethanol Intake during Periadolescence and Early Adulthood - Berardo, Luciana R.; Fabio, María C.; Pautassi, Ricardo M. (Frontiers in Behavioral Neuroscience, 2016)
This study analyzed ethanol intake in male and female Wistar rats exposed to maternal separation (MS) during infancy (postnatal days 1-21, PD1-21) and environmental enrichment (EE) during adolescence (PD 21-42). Previous work revealed that MS enhances ethanol consumption during adulthood. It is still unknown if a similar effect is found during adolescence. Several studies, in turn, have revealed that EE reverses stress experiences, and reduces ethanol consumption and reinforcement; although others reported greater ethanol intake after EE. The interactive effects between these treatments upon ethanol’s effects and intake have yet to be explored. We assessed chronic ethanol intake and preference (twelve two-bottle daily sessions, spread across 30 days, 1st session on PD46) in rats exposed to MS and EE. The main finding was that male – but not female – rats that had been exposed to EE consumed more ethanol than controls given standard housing, an effect that was not affected by MS. Subsequent experiments assessed several factors associated with heightened ethanol consumption in males exposed to MS and EE; namely taste aversive conditioning and hypnotic-sedative consequences of ethanol. We also measured anxiety response in the light-dark box and in the elevated plus maze tests; and exploratory patterns of novel stimuli and behaviors indicative of risk assessment and risk-taking, via a modified version of the concentric square field (CSF) test. Aversive conditioning, hypnosis and sleep time were similar in males exposed or not to environmental enrichment. EE males, however, exhibited heightened exploration of novel stimuli and greater risk taking behaviors in the CSF test. It is likely that the promoting effect of EE upon ethanol intake was due to these effects upon exploratory and risk-taking behaviors.